In vitro evaluation of Pandanus amaryllifolius ethanol extract for induction of cell death on non-hormone dependent human breast adenocarcinoma MDA-MB-231 cell via apoptosis - Chong Hueh; Yeap Swee; Rahmat Asmah; Akim Abdah; Alitheen Noorjahan; Othman Fauziah; Gwendoline-Ee Cheng (BMC, 2012)
Abstract Background Our previous study had shown that P. amaryllifolius was able to selectively inhibit cell proliferation of hormone independent breast cancer cell line MDA-MB-231. To understand the mode of killing and mechanism of action for P. amaryllifolius, the ethanol extract was evaluated for their alteration of cell cycle progression, PS externalization, DNA fragmentation and expression of anti/pro-apoptotic related protein. Results Cell cycle progression analysis, Annexin V and Tunel assays suggested that IC50 of P. amaryllifolius ethanol extract induced G0/G1 cell cycle arrest, PS externalization and DNA fragmentation. On the other hand, ELISA for cytochrome c, caspase-3/7, 8 and 9 indicated that apoptosis was contributed by mitochondrial cytochrome c release via induction of caspase 3/7, 9, and p53 was associated with the suppression of XIAP in P. amaryllifolius treated MDA-MB-231 cells. Conclusion Our findings suggest that P. amaryllifolius ethanol extract induced apoptosis on hormone independent breast cancer cell line MDA-MB-231.